2017
DOI: 10.1111/resp.13149
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gastric reflux on asthma in clinical practice

Abstract: CORRESPONDENCE Impact of gastric reflux on asthma in clinical practiceTo the Editors:Porsbjerg and Menzies-Gow reviewed the clinical impact of co-morbidities on severe asthma management. 1 The European Respiratory Society/American Thoracic Society (ERS/ATS) guidelines on severe asthma and the Global Initiative for Asthma (GINA) document recommend a systematic assessment of potential co-morbidities in all patients with possible severe asthma. 2,3 Co-morbidities may significantly affect asthma control, both aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
1
1
Order By: Relevance
“…The rates and risk ratios of asthma and GERD comorbidity reported in this Swedish adult twin population are commensurate with other large general population studies 8,35‐37 . In addition, our results support a number of studies which have found that GERD is a risk factor for asthma exacerbations and difficult to control asthma 3,38–41 . As far as we know our study is the first to report on asthma severity and GERD, the results do not support an association.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The rates and risk ratios of asthma and GERD comorbidity reported in this Swedish adult twin population are commensurate with other large general population studies 8,35‐37 . In addition, our results support a number of studies which have found that GERD is a risk factor for asthma exacerbations and difficult to control asthma 3,38–41 . As far as we know our study is the first to report on asthma severity and GERD, the results do not support an association.…”
Section: Discussionsupporting
confidence: 83%
“…8,[35][36][37] In addition, our results support a number of studies which have found that GERD is a risk factor for asthma exacerbations and difficult to control asthma. 3,[38][39][40][41] As far as we know our study is the first to report on asthma severity and GERD, the results do not support an association. These results suggest that GERD is more likely to be associated with an asthma exacerbation rather than severity of asthma as defined by high dose medications GINA guidelines Step 4 and 5.…”
Section: Ta B L Econtrasting
confidence: 84%
“…This may be due to poor inhaler skills and adherence or confounding comorbidities such as obesity and gastroesophageal reflux disease (GERD). Several studies have demonstrated an increased prevalence of GERD in asthma patients and highlighted its impact on asthma control 5 , 6 . Studies are needed to identify subgroups of asthmatic patients that may benefit from anti-reflux therapy.…”
Section: Introductionmentioning
confidence: 99%